Peran media sosial dalam pembentukan identitas keagamaan dan moderasi beragama generasi z muslim di indonesia - Baroya, Muh. Fikri Ainul (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the role of social media in shaping the character and identity of Muslim Generation Z in Indonesia. Social media has become an essential part of young people’s lives, serving as a means of communication, information, and self-expression, including in religious contexts. This research employs a descriptive qualitative approach with a library research method by analyzing literary sources such as scientific journals, articles, and books related to social media and the development of Muslim youth.The study finds that social media plays a significant role in shaping the Islamic identity of Generation Z, both through the dissemination of digital da’wah, the strengthening of religious values, and the formation of active online Muslim communities. However, social media also presents challenges, such as the spread of misinformation and the influence of global culture that may weaken Islamic values.